Meta-analysis of Vascular Imaging Features to Predict Outcome Following Intravenous rtPA for Acute Ischemic Stroke - Nogueira, Ricardo C.; Bor-Seng-Shu, Edson; Saeed, Nazia P.; Teixeira, Manoel J.; Panerai, Ronney B.; Robinson, Thompson G. (Frontiers in Neurology, 2016)
Background: The present review investigated which findings in vascular imaging techniques can be used to predict clinical outcome and risk of symptomatic intracerebral haemorrhage (sICH) in patients who underwent intravenous thrombolytic treatment. Methods: Publications were searched and inclusion criteria were as follows: 1) published manuscripts, 2) patients with acute ischemic stroke managed with intravenous rtPA, and 3) availability of imaging assessment to determine vessel patency or regulation of cerebral blood flow prior to, during and/or after thrombolytic treatment. Clinical outcomes were divided into neurological outcome (NIHSS within 7 days) and functional outcome (modified Rankin score in 2 – 3 months). sICH was defined as rtPA-related intracerebral bleeding associated with any worsening of NIHSS. Results: Thirty-nine articles were selected. Recanalization was associated with improved neurological and functional outcome (OR=7.83; 95% CI, 3.71 – 16.53 and OR=11.12; 95% CI, 5.85 – 21.14; p<0.001 respectively). Both tandem internal carotid artery/middle cerebral artery (ICA/MCA) occlusions and isolated ICA occlusion had worse functional outcome than isolated MCA occlusion (OR=0.26, 95% CI, 0.12 – 0.52; p<0.001 and OR=0.24, 95% CI, 0.07 – 0.77; p=0.016, respectively). Re-occlusion was associated with neurological deterioration (OR=6.48, 95% CI, 3.64 – 11.56; p<0.001) and early recanalization was associated with lower odds of symptomatic intracerebral haemorrhage (OR=0.36, 95% CI, 0.18 – 0.70; p=0.003) Conclusion: Brain circulation data before, during and after thrombolysis may be useful for predicting clinical outcome. Cerebral arterial recanalization, presence and site of occlusion, and re-occlusion are all important in predicting clinical outcome.